Dating Violence dan Kecenderungan Self Injury Pasangan Berpacaran - Astuti, Dara Nugrahaning; Meiyuntariningsih, Tatik; Ramadhani, Hetti Sari (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Individuals experiencing violence in romantic relationships are not limited to women alone; men also experience dating violence. This study aims to analyze the relationship between dating violence and the tendency for self-injury in early adults who are dating. This research falls under quantitative research, with 135 respondents included as subjects. The sampling technique used is purposive sampling, and the analysis employs the Pearson Product Moment correlation test. The results of this study indicate a significantly negative relationship between dating violence and self-injury in dating couples. Based on the research findings and discussions conducted, there is a highly significant negative relationship between dating violence and self-injury in dating couples. This means that the lower the dating violence in dating couples, the higher the tendency to engage in self-injury, and vice versa.